2017
DOI: 10.1002/prs.11897
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the initial pressure effect on methane‐air explosions in linked vessels

Abstract: This study experimentally addresses the pressure evolution during the closed and vented explosion progress of a methane‐air mixture ([CH4 = 10%]) in different vessel‐pipeline configurations at ambient initial temperature and different initial pressures. Based on the experimental measurements, it is found that the maximum values of both closed and vented explosion pressure increase linearly with the initial pressure in isolated and linked vessel scenarios. Compared with a vented explosion, the initial pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…After the borehole is filled with oxidizer, the initial pressure in the borehole ranges between 0.1 and 1 MPa. Experimental results have shown that the initial pressure has a significant effect on the maximum pressure of the gas explosion and the rate of surge development 19–22 . Therefore, this paper is based on practice, in the pressure range of 0.1–1 MPa in six groups to carry out experimental studies to obtain pressure, surge variation, and other data.…”
Section: Methodsmentioning
confidence: 99%
“…After the borehole is filled with oxidizer, the initial pressure in the borehole ranges between 0.1 and 1 MPa. Experimental results have shown that the initial pressure has a significant effect on the maximum pressure of the gas explosion and the rate of surge development 19–22 . Therefore, this paper is based on practice, in the pressure range of 0.1–1 MPa in six groups to carry out experimental studies to obtain pressure, surge variation, and other data.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous experimental and numerical studies on pressure piling have focused on a connected device and considered the initial pressure, container-length-to-diameter ratio, and pipe diameter as boundary conditions. Razus et al studied connected devices consisting of cylindrical vessels of volumes 1180 and 170 cm 3 and pipes of lengths 4.35 cm (inner diameter: 3.0-8.3 cm) and revealed that the pipe diameter was the primary factor affecting the explosion of the connected device, and the explosion pressure increased with the decrease in the pipe diameter [8,9]. Zhen et al investigated the influence of the initial pressure on the explosion pressure of the connected pipes using a connected device composed of spherical vessels with volumes of 0.113 and 0.022 m 3 and two pipes of lengths 2 m and inner diameter 0.06 m. The experimental results revealed that the explosion pressure increased linearly with the increase in the initial pressure [10].…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that changes in the structure of flameproof products could lead to pressure piling and interconnected structure, so that the explosion pressure increased instantly, flameproof enclosure internal structural changes would significantly change the explosion pressure. Chen et al [8] investigated the effect of wiring cavity on the explosion pressure of an flameproof motor. Through experimental analysis, the rotation state of the flameproof motor enhanced the turbulence.…”
Section: Introductionmentioning
confidence: 99%